Does working from home work in developing countries? - Mariana Viollaz (IZA World of Labor, 2022)
Work-from-home possibilities are lower in developing than in developed countries. Within countries, not all workers have equal chances of transitioning from the usual workplace to work-from-home. Moreover, infrastructure limitations and lack of access to certain services can limit the chances of effectively working from home. Having a home-based job can affect, positively or negatively, work-life balance, levels of job satisfaction and stress, and productivity. The differential chances of working from home may end up increasing the levels of income inequality between workers who can and those who cannot work from home.
Keywords: J22; J24; J28; J31; J81; 330; work from home; infrastructure and services constraints; work-life balance; productivity; income inequality